INTERNATIONAL WEEK TO SERVE CULTURES OF DIFFERENT NATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 26 November 2015 Universiti Sains Malaysia (USM) will be having its 10 International Week from 1 3 December 2015 and also the International Gala Night on 8 December 2015 at USM, to be jointly organised by the International Office (IO), Postgraduate Students Association, Desasiswa PETAS, Student Buddies and the Institute of Postgraduate Studies (IPS) USM.